A comparison of open and endovascular treatment strategies for the management of splenic artery aneurysms. (October 2016) - Sticco, Andrew; Aggarwal, Alok; Shapiro, Michael; Pratt, Abimbola; Rissuci, Donald; D'Ayala, Marcus
Splenic artery aneurysms are rare with an incidence of less than 0.8%. Evidence to support an endovascular management strategy over open surgical repair for SAA is limited. We used the Nationwide Inpatient Sample to compare open to endovascular SAA repair by assessing postoperative outcomes, length of hospital stay, and mortality. Multivariate logistic regression analysis was done to determine predictors of postoperative complications. There were 2316 admissions with a diagnosis code for SAA [347 (14.9%) endovascular repair and 112 (4.8%) open surgery]. There was a statistically significant lower rate of cardiac (2.3% vs 6.9%, P = 0.05) and pulmonary (8.9% vs 16.1%, P = 0.05) complications for the endovascular repair group. The risk of surgical site infection was also lower (0.6% vs 5.1%, P = 0.01) in the endovascular group. Median in-hospital LOS was greater for open repairs (6 vs. 4 days, P = 0.01). There were no statistically significant differences across procedures for renal complications (8.9%, P = 0.88) or in-hospital mortality (3%, P = 0.99). Regression analysis established procedure type to be independent predictor of postoperative complications. Endovascular repair of SAA is therefore associated with a lower complication rate and less resource utilization but no difference in mortality peri-operatively. This may justify an endovascular first treatment strategy in the management of SAA.